Improved microstructure and mechanical properties of sheet metals in ultrasonic vibration enhanced biaxial stretch forming - Nima Najafizadeh; Majid Rajabi; Ramin Hashemi; Saeid Amini (Journal of Theoretical and Applied Vibration and Acoustics, 2019)
Ultrasonic energy is used for applying severe plastic deformation on metal surfaces. In the present work, the effect of ultrasonic vibration on the formability, microhardness and microstructural properties of St14 steel sheet has been investigated. To be precise, a semi-hemispherical-head forming tool had shaped the specimens until the necking started to happen. Conventional as well as the ultrasonic-assisted biaxial stretch forming test has been performed on St14 steel sheets and obtained data has been used to compare the hardness and microstructure of the specimen with and without superimposing the ultrasonic vibration. It was observed that the hardness of the samples which have been shaped by applying ultrasonic vibrations to the tool with an amplitude of 15µm at 20.5 kHz increased significantly in compared with the samples which have been shaped without using ultrasonic vibration, revealing the efficiency of the ultrasonic operation in increasing the hardness.